Molecular sexing of IVF and in vivo derived embryonic cell colony in goat - RANJAN, R; DAS, B C; BAG, SADHAN (The Indian Journal of Animal Sciences, 2013)
The present study was designed to standardize the molecular sexing of caprine embryos from few blastomere of IVF- and in vivo- derived embryonic cell colony in one step by real time PCR. The cumulus oocyte complexes (COC) were isolated, evaluated, graded and matured in maturation media and after maturation, the oocytes were incubated with 50μl capacitated spermatozoa of proven buck from experimental shed of this institute for IVF embryo production. Surgical embryo collection was done from 10 goats as per standard protocol and mated with a buck of proven fertility. Embryonic stem cell culture method was used for generation of embryonic cell colony from IVF- and in vivo- derived embryos of 8–16 cells and morula. Genomic DNA was isolated from blood sample for standardization of SRY gene expression. Genomic DNA was also isolated from 8–16 cell and morula stage of in vivo and IVF derived embryonic cell colony. Sexing of IVF- and in vivo- derived embryonic cell colony was done with SRY gene expression using real time PCR. The sex ratio of male: female embryos were 1: 1.5 and 1: 1 in 8–16 cell and morula stage in vivo- embryo derived embryonic cell colony respectively. For IVF embryos the sex ratio of male: female was 1: 1.25 and 1.1: 1 in 8–16 cell and morula stage of derived embryonic cell colony respectively. The overall sex ratio of male: female embryos were 1: 1.18 in our study.